Identifikasi Keberhasilan dan Pengaruh Kemampuan Manajerial Pelaku Program Pengembangan Kecamatan di Wilayah Kabupaten Klaten - Eka Sudarusman; Nur Rokhman (Telaah Bisnis, 2016)
Abstract One of the effort in combating poverty and urban community created by the government is the community empowerment and development program those are, Program Pengembangan Kecamatan (PPK) or Program Nasional Pemberdayaan Masyarakat (PNPM). The PPK/PNPM expected to accelerate poverty eradication and sufficiency society based on the development by increasing public capacity, local government; and the provision of facilities and the social economy infrastructures. The research identifies the PPK/PNPM success both in the main economic indicators and the managerial skill. The success indicators program consist of: increasing revenue (income indicator), poverty reduction, efficiency in program deliver, and financial viability. The research obtained primary and secondary data. The primary data will be analyzed with quantitative analysis with Mann-Whitney u test, and the secondary data will be analyzed comparing with success indicators index.The reseach output indicates that average income indicator 10,59%, poverty reduction 9,48%, average efficiency in program delivery 10,59% and financial viability 11,51%. The managerial skill indicates have influenced to the succes of the program.